Export marketing strategies for the Northern Ireland seed potato industry - Lamont, Jeffrey (Cranfield University, 1989)
This thesis is concerned primarily with the export marketing performance of the Northern Ireland seed potato industry. The Industry has shown a dramatic decline in exports over the past twenty years, and this thesis proposes strategies aimed at regaining, and maintaining, a competitive advantage for the industry in world markets. A comparative analysis is conducted of the strategic and organisational export capabilities of the Northern Ireland industry and its main competitors. In addition, an analysis of the requirements of major world seed potato markets is undertaken. Academically, the thesis aims to apply the principles of export marketing to a traditionally managed sector of agriculture. As such, it is hoped that the thesis makes a useful contribution to the literature on agricultural marketing and export marketing. Major academic themes explored in the thesis include - Globalisation versus 'customisation' - New product development strategy and export success - Product-life-cycle analysis and product-enhancement strategies - Export promotional strategies - The utility of horizontal and marketing performances - 'Market spreading' versus 'key market concentration' vertical integration in enhancing - Centrality or peripherality of the export function The central hypothesis explored in the thesis is that in an agricultural industry, such as a seed potato one, where production is fragmented over a. large number of small production units, then a necessary prerequisite to successful strategic exporting is the existence of an appropriate organisational structure to carry out the strategic tasks. This hypothesis is confirmed by the findings of the research. As the product and service requirements of world seed potato markets have changed over the years, and are becoming more sophisticated, the Northern Ireland industry has been unable to adopt an appropriate customisation strategy in response. This is due to the inhibiting effect of an inappropriate organisational structure within the industry. By way of contrast, industries which have developed considerably by responding to changing market requirements (such as the Netherlands, France and Scotland) are characterised by a strongly integrated organisational structure (both horizontal and vertical). In all these countries this has largely been achieved by the development of marketing co-operatives. In seeking to propose export marketing strategies for the Northern Ireland industry therfore, a necessary prerequisite is to establish an appropriately integrated organisational system within the industry. As the seed potato marketing co-operative Expotato Limited has already begun to introduce a horizontally and vertically intergrated discipline into the Northern Ireland industry, it is suggested that this co-operative should be further developed as a catalyst for positive organisational and strategic development of the industry ...[cont.].